Case Study of Remaining Service Life Assessment of a Cooling Water Intake Concrete Structure in Indonesia - M. Sigit Darmawan; Ridho Bayuaji; N. A. Husin; R. B. Anugraha (Advances in Civil Engineering)
This paper deals with the assessment of remaining service life of a cooling water intake concrete structure (CWICS) subjected to corrosion due to chloride attacks. Field and laboratory tests were performed to determine the current existing condition of the structure. Both destructive and nondestructive tests were employed to obtain the parameter needed for the assessment. Based on the current condition and test results, structural analysis was carried out and the remaining safety factor of CWICS was determined. From the analysis, it was found that most concrete elements of CWICS had safety factor greater than unity and might fulfil its intended service life up to the year 2033. However, fewer elements require immediate strengthening to extend their service life.